2000
DOI: 10.1038/sj.ejcn.1601104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a probiotic milk product on plasma cholesterol: a meta-analysis of short-term intervention studies

Abstract: Introduction: Certain fermented dairy milk products may have bene®cial effects on plasma cholesterol levels. However, a number of studies have produced con¯icting results as to whether dietary supplementation by a probiotic dairy product containing the bacteria culture Causido 1 reduces plasma cholesterol. Objective: To conduct a meta-analysis of intervention studies to evaluate the effect of the Causido 1 culture on plasma total cholesterol and low-density lipoprotein (LDL)-cholesterol. The probiotic milk pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 5 publications
6
90
1
3
Order By: Relevance
“…Even though no overall significant differences in the HDL:LDL ratio was found, it cannot completely be rejected that the increase in HDL and decrease in LDL from baseline to the end of the intervention in the 10 10 CFU/day group, could have a clinical prophylactic effect in healthy, normocholesterolemic individuals or people with elevated cholesterol levels. In general, the duration of studies showing effect on blood lipids seem to be of longer duration than the present (Agerholm-Larsen et al, 2000a).…”
Section: Discussionmentioning
confidence: 51%
“…Even though no overall significant differences in the HDL:LDL ratio was found, it cannot completely be rejected that the increase in HDL and decrease in LDL from baseline to the end of the intervention in the 10 10 CFU/day group, could have a clinical prophylactic effect in healthy, normocholesterolemic individuals or people with elevated cholesterol levels. In general, the duration of studies showing effect on blood lipids seem to be of longer duration than the present (Agerholm-Larsen et al, 2000a).…”
Section: Discussionmentioning
confidence: 51%
“…In contrast to our findings, previous meta-analyses reported that probiotics effectively reduced the levels of TC and LDL cholesterol in subjects with originally high or normal lipid levels. 43,44 This discrepancy may result from the characteristics of the study group (healthy or obese subjects in previous analyses vs subjects with diabetes in our meta-analysis), the length of intervention, or the choice of probiotic strain.…”
Section: Probiotics and High-density Lipoprotein Cholesterol Levels Omentioning
confidence: 78%
“…For example, Andersson and Gilliland (117) found a significant reduction in total cholesterol in fourteen hypercholesterolaemic subjects when consuming Lactobacillus acidophilus L1, a human-derived strain, compared with L. acidophilus ATCC 43121, isolated from the porcine gut. Agerholm-Larsen et al (124) reported a metanalysis of studies using the probiotic fermented milk Gaio ® , containing Enterococcus faecium (with the potential probiotic activity) and two strains of Streptococcus thermophilus for milk acidification. From six studies using this product, the authors concluded that short-term intake (4-8 weeks) of this fermented milk produced significant lowering of total and LDL-cholesterol (by 4 and 5%, respectively) but that further studies were required to confirm any long-term effects.…”
Section: Reducing Cvd Risk With Probioticsmentioning
confidence: 99%